Pengujian Alat Press Hidrolik Kapasitas 20 Ton - Novis, Iskan; Muknizar, Muknizar; Risal Abu; Zulkarnain, Zulkarnain; Azmil Azman (Fakultas Teknik UMRI, 2023)
A manual hydraulic press is a tool that functions to press or press work objects and this tool is equipped with a pressure measuring device. This research is to determine the parameters of the test results of a 20 ton capacity hydraulic press on different specimens, namely: ST 37 shaft, ST 41 shaft and ST 60 shaft with the same diameter, namely 13 mm. The results of the test, the first test of the ST 37 shaft produced a pressure of 1000 Psi/ 70.307 kg/cm². With a change in diameter of 0.4 mm, the cross-sectional area is 0.00001256 m², and the total pressure force is 195,311 N. The second test on the ST 41 shaft produces a pressure of 1300 Psi/ 91,399 kg/cm². With a change in diameter of 0.3 mm, the cross-sectional area is 0.000007065 m², and the total pressure force is 195.105 N. The third test on the ST 60 shaft produces a pressure of 1600 Psi/ 112.4911 kg/cm². With a change in diameter of 0.1 mm, the cross-sectional area is 0.000000785 m², and the total pressure force is 194.898 N.